Analysis of the Influence of Price and Product Variation on Consumer Buying Interest at Tjap Djajakarta Malang - Akbar, Muhammad Alfaisal; Rachmi, Asminah (CV. Proaksara Global Transeduka, 2024)
Two key factors that play a crucial role in the growth of Tjap Djajakarta Malang are the diversity of prices and products. The aim of this research is to investigate how Price and Product Variations impact Consumer Buying Interest in Tjap Djajakarta Malang, both individually and collectively. This study employed quantitative methods, focusing on two independent variables: Price (X1) and Product Variations (X2). The dependent variable in this study was Buying Interest (Y). Questionnaires were utilised to collect data from a sample of 98 respondents, selected using purposive sampling techniques. The analysis of the data included multiple regression, determination of coefficients, and testing of hypotheses. According to the results of the t-test (partial), the first hypothesis (H1) has been confirmed. This suggests that the price factor (X1) has a partially positive effect on purchasing interest at Tjap Djajakarta. The second hypothesis (H2) has also been supported. This indicates that the product variety factor (X2) partially influences purchasing interest at Tjap Djajakarta Malang. Upon conducting the F-test (simultaneous) for the third hypothesis (H3), it was found that H3 is accepted while H0 is rejected. Therefore, it can be inferred that both price and product range have a combined positive impact on consumer interest at Tjap Djajakarta Malang. Based on the findings of this study, it is recommended that Tjap Djajakarta retains its pricing strategy and expands its product offerings to attract more customers and become their preferred option.